METODE DOPPLER RADIO UNTUK MENGUKUR KECEPATAN ROKET RX200 [RADIO DOPPLER METHOD FOR MEASURING VELOCITY OF ROCKET RX200] - Widada, Wahyu (BRIN Publishing, 2012)
This paper discusses the methods and design of radio Doppler to measure the speed of the rocket type RX200. Doppler system consists of a radio transponder to emit a continuous radio signal from the rocket and the radio base station to measure the change in frequency of the radio signal. A change in the frequency of the radio signal caused by the speed of the rocket is used to measure the speed and position of the rocket. The design of radio frequency is 880 MHz transponder adapted to the design speed of the rocket RX200. This method is relatively easy to implement compared with the radar transponder system that has been developed. A simulation of Doppler frequency is performed using the radar data transponder rocket launch experiment RX200 and recomendation of bandwith radio receiver should be 4000 Hz. The combination of these two systems will make a more acurate and reliable tracking system.